Novel Transdural Epiarachnoid Approach for Large Central Disk Herniation in Upper Lumbar Spine. Issue 1 (January 2022) - Nishikawa, Hirofumi; Fujimoto, Masashi; Tanioka, Satoru; Ikezawa, Munenari; Nakatsuka, Yoshinari; Araki, Tomohiro; Suzuki, Hidenori; Mizuno, Masaki
Abstract : BACKGROUND AND IMPORTANCE: The treatment for large central disk herniation (LCDH) at upper lumbar spine is often challenging. Previous reports showed various surgical strategies, such as microdiscectomy with posterior fixation, endoscopic surgery, and microdiscectomy through transdural approach. However, there is no consensus regarding which surgical option is better for LCDH at upper lumbar spine. In this report, we describe the novel transdural epiarachnoid approach (TDEA), which uses the corridor of epiarachnoid space for microdiscectomy. Compared with classical transdural approaches, this novel approach may reduce risks of postoperative cerebrospinal fluid leakage and the development of arachnoiditis. CLINICAL PRESENTATION: A 69-yr-old man presented with progressive bilateral radiating leg pain, intermittent claudication, and low back pain. Magnetic resonance images and computed tomography scans revealed LCDH at L2/3 level. We performed microdiscectomy using the TDEA. Postoperative course was uneventful, and his symptoms were relieved after surgery. CONCLUSION: The novel TDEA for LCDH at upper lumbar spine is illustrated with a video. This novel approach has an advantage of the preservation of subarachnoid components compared with classical transdural approaches.